Solid Waste Disposal and Extent of Selected Heavy Metals in Fadama Area of Sokoto City, Nigeria - Yusuf Sarkingobir; Umar Tambari; Aminu Umar Imam; Marwanu Abubakar; Mustapha Sahabi (Journal of Bioresources and Environmental Sciences, 2023)
This study was carried out with the purpose of assessing solid waste disposal and levels of heavy metals in Fadama area of Sokoto city. A survey using questionnaire and atomic absorp-tion spectroscopy was employed for the study. The descriptive statistics and X2 test were done. The types of pollution noticed include: land (40.0%), air (40.0%), and water (20.0%). The possible causes of the pollution include, mostly open dumping of solid waste (41.7%), then open defecation (33.3%), and lastly burning (25.0%). Spread of diseases was most (40.0%) perceived effect, then effect on children (20.0%) and gastroenteritis (20.0%). Other effects are: sickness (13.3%) and accidents (6.7%). The efforts to address the waste disposal are: burning (60.0%), pushing it away from road (20.0%) and provision of containers (20.0%). Effort did by the government involves, promising to bring con-tainers (30.0%), and doing nothing (70.0%). Wastes found are: plastics (70.0%), organic and defeca-tions (23.3%), metal and relations. The heavy metals analysis shows, the lead ranges from 5.1 ± 1.2 to 10.0 ± 0.80 (ppm); chromium ranges from 0.59 ± 0.01 to 2.10 ± 0.02 (ppm); zinc ranges from not detected to 0.81 ± 0.3 (ppm); cadmium from 0.25 ± 0.02; and mercury ranges from 0.95 ± 0.02 to 10.20 ± 0.11 (ppm). There is poor waste management in an agricultural area, a trend that can seep harmful chemicals to be taken up by plants to the upward food chain/web, coupled with other harmful ef-fects of waste such as instigation of diseases and environmental degradation.